The Effect of Double Loop Problem Solving Integrated Jelajah Alam Sekitar to Improve Students' Scientific Literacy and Critical Thinking - Khasanah, Khumairotul; Irsadi, Andin (Universitas Negeri Semarang, 2025)
Indonesian students' scientific literacy in PISA 2022 experienced decline of 396 (PISA 2018) to 383 points. SMAN 1 Sragi's learning is limited to PPT-assisted lectures and Covid-19 causes students' cognitive decline so that students' scientific literacy and critical thinking need to be optimized through JAS integrated DLPS in environmental change material. The aim research are to analyze the form of integration of DLPS with JAS, analyze the effect of implementing JAS integrated DLPS and analyze the effectiveness of JAS integrated DLPS. Pre-Experimental in the form of one group pretest-posttest design. The results show that JAS integrated DLPS has positive effect on increasing students' scientific literacy and critical thinking and the N-Gain value is ≥ 0.60 in all aspects of scientific literacy and critical thinking. Three criteria for testing the effectiveness of JAS integrated DLPS, namely 79% of students scored ≥75 on scientific literacy and 94% on critical thinking. Second, the N-Gain value for scientific literacy is 0.71 (high) and critical thinking is 0.77 (high). Third, the Wilcoxon test is significant. The conclusion are the form of integration of DLPS with JAS consists of the syntax of problem identification, initial detection, tentative solutions, causal analysis, root problem detection and designing main solution to problem; implementation of JAS integrated DLPS has positive effect on increasing students' scientific literacy and critical thinking; and JAS integrated DLPS is significantly effective in increasing students' scientific literacy and critical thinking on environmental change material.